2005
DOI: 10.1111/j.1439-0418.2005.01001.x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of chorionic malformations and insecticide resistance by Spodoptera exigua

Abstract: Effect of exposure to the organophosphorus insecticide -fenitrothion [O,O-dimethyl-O-(4-nitro-3-methyl)phenyl] -on four generations of Spodoptera exigua Hu¨bner (Lep., Noctuidae) larvae, with regard to the mortality and structure of the chorion of eggs laid was tested. Generations varied in the total mortality rate, although all of them showed some survival rate. The third and the fourth generations showed the lowest mortality among tested ones. Exposure to fenitrothion caused malformations in eggs. The chorio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
3
7
0
Order By: Relevance
“…Cracks around the micropylar and aeropylar regions were very similar to those observed in the present study. In order to understand the interaction between the inheritance of chorionic malformations and the insecticide resistance of S. exigua, Adamski et al (2005) studied the eggs of this insect and observed deposition of abnormal material in the chorion that was very similar to that observed in the present study. Since the cement layer of the chorion is composed of lipoproteins and organophosphate pesticides have, in general, the ability to cause disturbances in protein metabolism, the authors suggested that disturbances in the cement glands of females caused by the pesticides, could explain chorion malformation.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Cracks around the micropylar and aeropylar regions were very similar to those observed in the present study. In order to understand the interaction between the inheritance of chorionic malformations and the insecticide resistance of S. exigua, Adamski et al (2005) studied the eggs of this insect and observed deposition of abnormal material in the chorion that was very similar to that observed in the present study. Since the cement layer of the chorion is composed of lipoproteins and organophosphate pesticides have, in general, the ability to cause disturbances in protein metabolism, the authors suggested that disturbances in the cement glands of females caused by the pesticides, could explain chorion malformation.…”
Section: Discussionsupporting
confidence: 75%
“…These changes could be detected for both peel and leaf extracts at lowest concentration (300 µg/ml). Meanwhile, a search for correlation between egg abnormality and hatching was not carried out since the arrangement of S. frugiperda eggs in layers does not allow the quantitative determination of malformed eggs (Adamski et al, 2005).…”
Section: Ultrastructural Analysis Of Eggs From S Frugiperdamentioning
confidence: 99%
“…Pesticides can be harmful to many non-target species and sublethal concentrations may cause side-eVects on population development due to reproductive disturbance (Debnath and Mandal 2002;Adamski et al 2005), change of DNA structure (Moretti et al 2002) and ultrastructural abnormalities (Mehlhorn et al 1999(Mehlhorn et al , 2001. Some papers describe a decrease in numbers of soil invertebrate fauna exposed to various pesticides (Chakravorty et al 1995;Joy and Chakravorty 1991;Vig et al 2006).…”
Section: Introductionmentioning
confidence: 96%
“…We may suggest that the best time to control this pest would be after spinach is harvested from the fields and the pest population has moved back to their natal host or another auxiliary host. But it all depends on the physical characteristics of the varieties, such as trichomes and glossy surfaces which certainly do not favor the lepidopteron pests (Adamski, Niewadzi, & Ziemnicki, 2005;Adamski et al, 2009;Ahmad et al, 2007;Álvarez, Pera, Loto, Virla, & Baigori, 2009;Álvarez-Alfageme, Ortego, & Castañera, 2009;Antwi & Peterson, 2009;Atwal & Dhaliwal, 2013;Javed, Aziz, & Leghari, 2009).…”
Section: Discussionmentioning
confidence: 99%